Surface-based air defense system analysis - Macfadzean, Robert H. M.; Johnson, James Michael, 1946-; Macfadzean, Robert H. M. (Norwood, MA : Artech House, 1992)
Provides six modules for the analysis of air defense systems.
1. Anti-aircraft artillery analysis -- 2. Autopilot and airframe dynamics -- 3. Proportional navigation guidance accuracy -- 4. Missile envelope model -- 5. Mission model programs -- 6. Campaign model.
Title from user's guide.
Intended to be used with book of the same title by Robert H.M. Macfadzean.
Copy-protected.
Engineers.
System requirements: IBM AT, XT, or 386; 512K RAM; MS-DOS 3.0 or higher; 1 disk drive and hard disk; CGA, EGA, VGA adapter; math coprocessor (optional).
LC has 2 copies and printout of source code for program.
Keywords: Air defenses -- Software; Surface-to-air missiles -- Software